The difficulties of research in the social history of cinema: Alba de América (Orduña, 1951) - Gil Gascón, Fátima; Chicharro Merayo, Mar; Gómez Segarra, Manuel (Cuadernos de Documentación Multimedia, 2024)
The purpose of this article is to analyze the problems with which research into the social history of cinema must contend eby studying the film Alba de América (Dawn of America) (Orduña, 1951). This movie, which narrates the discovery of America, is considered one of the Regime's leading works of historical propaganda. The academic literature states that it was produced in response to the English film Christopher Columbus (McDonald, 1949) and that important characters such as Carrero Blanco were involved in its production. In order to corroborate these statements and discover omissions existing in terms of the film, we reviewed documentation related to its production. This led to detection of some of the challenges with which all researchers on this topic must grapple: assumption of approaches historically considered to be true, but not confirmed, diverging interests in thematic descriptors of archives, and difficulty in accessing certain collections. Although the research is incomplete, since we were unable to access part of the documentation, the information we found corroborates the need for better and greater access to archives, as well as a more impartial look at Francoist cinematography.
Keywords: Cinema; Francoist time; Alba de América; Social history of cinema; Cliched; Archives